Pemikiran Imre Lakatos (1922-1974) tentang Metodologi Program Riset dan Signifikansinya dalam Kajian Keislaman - Ahmad Amir Aziz (Islamica: Jurnal Studi Keislaman, 2006)
Apart from Kuhn and Popper, Lakatos has become an important figure in thefield of Philosophy of Science for his scientific theories, which he calls researchprogrammes. For Lakatos, Popper?s theoretical falsification can be immensely dangerouswhen applied to the already established theories. On the other hand, in contrast to Kuhnwho assumed that a paradigm is by its nature immeasurable, Lakatos maintains that thecompeting scientific discoveries may in fact be compared between one another. To him,the main issues with regard to the logic of discovery cannot be dealt with satisfactorilyunless we do so within the framework of research programmes. The practicalimplementation of this would be that the hard core of this framework cannot be subjectedto modification -let alone- rejection. This hard core must in other words be protectedfrom what he terms falsification. Lakatos also maintains that what can be said as scientificis a series of theory, and not a single theory. This model of research programmes can infact be used in Islamic Studies in order to develop new theoretical principles that mayplay a role of convincing protective-belt on the one hand, and to find new premiseswhose discoveries can be used universally on the other